Unpacking identity construction and negotiation: A case study of Chinese undergraduate students' social and academic experiences while studying abroad. (November 2022) - Cai, Yanling; Fang, Fan; Sun, Honghong; Jiang, Lianjiang
Abstract: The complexity that arises between linguistic use and cultural identity during learners' study abroad experience has been emphasised to understand learner investment and learner agency. Anchored in a social view of learner agency and identity, this study used qualitative research methods to unpack the identity construction and negotiation of Chinese students studying abroad by investigating their agencies, investment, and identity construction and negotiation. Data were collected through semi-structured interviews and narrative journals from Chinese university-level students with study abroad experiences in countries where English is used as the dominant language. Using learner agency, attitude and construction of identity, and identity negotiation through intercultural conflicts as the analytical lens for data analysis, the findings showed that the participants experienced identity reconstruction by investing in their linguistic resources and practices and enacting their agency. Moreover, the participants' study abroad experiences enabled them to develop a new way to invest in language learning and use, partly change their language attitudes towards accents and negotiate their identities through intercultural conflicts, which influenced the reconstruction of their previously imagined identities of native speakers of English. The study has important implications for teaching English as a second language and for preparing students to study abroad.